Pentingnya peran orang tua dalam meningkatkan motivasi belajar - Fitriyani, Putri Diyah (Maliki Interdisciplinary Journal, 2024)
The motivation to learn is a crucial factor in determining a child’s academic success. Besides internal factors, external factors such as parental involvement also play a significant role in shaping a child’s motivation to learn. This study examines the importance of parental involvement in enhancing a child’s motivation to learn through three key aspects: creating a conducive learning environment, actively participating in the child’s learning process, and building the child’s self-confidence and self-esteem. Parents can create a comfortable learning environment by providing a dedicated study space, minimizing distractions, and ensuring adequate learning resources. Active involvement in helping with homework, discussing lesson material, and participating in school activities is also crucial. Additionally, emotional support through praise, constructive feedback, and emphasizing the importance of the learning process is essential in building the child’s self-confidence and self-esteem. By implementing these strategies, parents can create a supportive learning environment, provide academic guidance, and strengthen their child’s motivation to learn, ultimately leading to improved academic performance. Key Terms: